Improving the Thermochemical Heat Storage Performance of Calcium Hydroxide in a Fixed-Bed Reactor by Y-Shaped Fins - Guangyao Zhao; Zhen Li; Jiakang Yao; Zhehui Zhao; Sixing Zhang; Na Cheng; Lei Jiang; Jun Yan (Buildings)
Thermochemical heat storage technology has great development prospects due to its high energy storage density and stable long-term storage capacity. The calcium hydroxide/calcium oxide reaction has been proven to be feasible for thermochemical heat storage. However, due to its low thermal conductivity, the slow heat storage reaction in the fixed-bed reactor needs to be improved. In this work, the Y-shaped fin was used to improve the heat storage performance, and a multi-physics numerical model was established for its heat storage process in the fixed bed. The results show that the Y-shaped fin can accelerate the heat storage reaction due to the improved heat transfer inside the reactor. The heat storage time decreases by 45.59% compared to the reactor without a fin and it decreases by 4.31% compared to the reactor with the rectangular fin. The increase in the wall temperature of the heating tube and the thermal conductivity of the fin can improve the heat storage performance; moreover, the Y-shaped fin shows more performance improvement than the rectangular fin at high wall temperature or thermal conductivity. The increase in porosity of heat storage material can shorten heat storage time due to the reduction in reactant, and the Y-shaped fin can still give a better performance than the rectangular fin at different porosity levels. This work can provide a reference for improving the heat storage performance of fixed-bed reactors.